Aquel maravilloso trozo del solar patrio : Spain in Equatorial Guinea, between colonial representations and hispanization (1778-1931) - (:unkn) unknown (My University, 2019)
In the 1830s, the Spanish designs on Equatorial Guinea brought about the development of a very diverse literature - scientific papers, missions, travel stories, opinion pieces, etc.. - through which emerges a curiosity, a certain way of looking at black Africa and its people. The installation of a Spanish government from 1858 was obviously promoting, on the fringe of colonial activities that are outside of our field of research, information flow and the movement of Spanish people. Several scientific journals about black Africa were born in Spain, and religious missions developed. We propose to study these new relationships that develop between Spain and Western Sub-Saharan Africa during the end of 18th and the early 20th century by leveraging these materials to multiple interest: scholarly publications, scientific and military journals, newspapers, travelogues, documentation from religious missions, as well as graphic material - illustrations in the press in particular. Giving to our future thesis the title Aquel maravilloso trozo del solar patrio: l'Espagne en Guinée Équatoriale, entre représentations coloniales et hispanisation (1778-1931), we intend to highlight two key aspects of our future research: - Firstly, double entry, inter-cultural and inter-ethnic -secondly, the perspective of both discursive and representations that we want to embrace. We want to put us in-between a confrontation and exchange where speech and imaginary constantly interpenetrate. Rather than consider a historical study of the Spanish presence and domination in black Africa, which already has a fairly extensive bibliography, the question is to see, from an essentially cultural analysis, how Iberian world and sub-Saharan African rub and discover each other. In sum, what interests us is to analyze the interplay that occurs between colonizers and colonized, not through the description of the objective conditions of the Spaniards and Africans or according to the vaga
Keywords: African Research